Proses Masuknya Islam di Maluku dan Papua - Masdiana Silvia Sinaga; Pebina Kaban, Yeza; Salomo Pardosi , Christian; Andika Nainggolan , Nahot; Suhendro Lukitoyo , Pristi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The process of Islam’s arrival in the Maluku Islands and Papua is a crucial element in the history of the spread of Islam in eastern Indonesia, which occurred gradually and peacefully. This study aims to analyze the routes, key figures, and social and cultural dynamics that influenced the spread of Islam in these two regions. The method employed is a literature review using a historical approach, through the analysis of various references and findings from previous research. The findings indicate that Islam began to appear in the Moluccas as early as the 13th century via trade routes involving merchants from Arabia, Gujarat, and other parts of the Indonesian archipelago. The role of kingdoms such as Ternate and Tidore proved to be crucial in accelerating the spread of Islam in the region.